Analisis Sistem Pengendalian Intern Terhadap Pengelolaan Kas pada Institut XYZ - Miftahuljannah, Anisyah; Shahib, Habib Muhammad (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2024)
This study aims to analyze the effectiveness of the internal control system in cash management at XYZ Institute. The background of this research is based on the importance of good internal control to maintain the liquidity and financial efficiency of private universities, especially in the face of funding challenges and limited student growth. The research method used includes descriptive analysis with a qualitative approach, involving data collection through interviews and direct observation.The results showed that although Institut XYZ had implemented several internal control components in accordance with the COSO framework, there were still weaknesses in the implementation and monitoring of the system. These weaknesses have the potential to disrupt cash management and increase the risk of errors and fraud. This study recommends improvements in internal control procedures and increased human resource capacity to achieve the goal of more effective cash management.